Fenomena Radikalisasi Digital di Indonesia dan Implikasinya Terhadap Kebijakan Kontraterorisme di Asean - Rina Sabrina (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
Digital radicalization has emerged as a strategic phenomenon that reshapes the landscape of national and regional security threats, particularly in Indonesia and the Southeast Asian region. This study aims to analyze how state actors construct the securitization process of digital radicalization and how this threat framing influences ASEAN's counterterrorism policies. Employing a qualitative approach with a case study method, the research examines data from academic literature, national and regional regulations, and expert interviews on security policy. The findings reveal that securitizing actors such as Indonesia’s National Counterterrorism Agency (BNPT) and Densus 88 frame extremist digital activities as existential threats, prompting extraordinary measures such as website blocking, cyber surveillance, and the enactment of specific regulations, notably Law No. 5 of 2018. At the regional level, this narrative gains legitimacy through the ASEAN Convention on Counter Terrorism (ACCT), which serves as a collaborative framework among member states to address transnational terrorism. However, the effectiveness of ASEAN’s policy response continues to face significant challenges, including technological capacity gaps, the absence of collective enforcement mechanisms, and tensions between security imperatives and civil liberties. This study concludes that digital radicalization requires vertical integration between national and regional policies, alongside a hybrid approach that balances hard and soft security instruments. To that end, ASEAN must reorient its counterterrorism strategy by strengthening digital security capacities, expanding value-based counter-narratives, and enhancing cross-sectoral coordination to build regional resilience against adaptive and transnational threats.